Institutional Localization in Databases: Institutional Localization Model in PubMed Database via LinkOut Service - Binici, Kasım (Information World, 2011)
PubMed is a database that most heavily used in the field of medicine and health sciences. It is a bibliographic database and also allows access to the full text via LinkOut service. In a result of the search in PubMed, LinkOut gives links from the bibliographic records to full text providers, and also shows full text articles that owned by the library. This method defined as “institutional localization”. In this implication, it is shown full text providers and library via a link in a logo. This service means of the fast, easy and efficient access to the information for end users.In this study, it is explained institutional localization in PubMed database via LinkOut. It is also emphasized how can use this services medical libraries or medical institutions providing access to information.
Keywords: Localization; Institutional Localization; Personalized Resource Management Program; PubMed; LinkOut